High-purity silica sol for chemical mechanical polishing and preparation method thereof
By adding sodium polyacrylate and thirteen fluorinel oxygenosililane to silicon -soluble preparation, and the ladder heating program is used to solve the problem of easy reunion and settlement of silicon -soluble, it improves the polishing effect and service life.
Patent Information
- Application Number
- CN202411443512.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-10-16
AI Technical Summary
Existing silicone sols are prone to agglomeration and settlement in applications, affecting the polishing effect and service life.
By adding sodium polyacrylate and tridecafluorooctyltriethoxysilane during the preparation process of silica sol, and adopting a step temperature rising program, the growth and dispersion of silica particles are controlled to prevent agglomeration and sedimentation.
The stable dispersing of silicon -soluble, improving the polishing effect and resistance to settlement, extending the service life.
Smart Images

Figure BDA0005087035960000081 
Figure BDA0005087035960000091
Abstract
Description
Technical Field
[0001] The invention relates to a silica sol and a preparation method thereof, in particular to a high-purity silica sol for chemical mechanical polishing and a preparation method thereof. Background Art
[0002] With the rapid development of semiconductor industry, microelectronics manufacturing, optical instruments and precision machining, higher and higher requirements are placed on the flatness and finish of material surfaces. As an important surface treatment technology, chemical mechanical polishing (CMP) technology has been widely used in these fields for its high efficiency and precise polishing effect. CMP technology achieves ultra-smooth processing of workpiece surfaces through the synergistic effect of chemical oxidation and mechanical friction, greatly improving the quality and performance of products.
[0003] In CMP technology, polishing liquid is a crucial component, and silica sol, as one of the main components of polishing liquid, has unique advantages. Silica sol is a colloidal dispersion formed by nano-SiO2 particles dispersed in water (or organic solvents). Its internal Si-O-Si bond structure gives it good stability and dispersibility. In addition, SiO2 abrasives have the characteristics of moderate hardness, small particle size, large specific surface area, and excellent permeability. These characteristics make silica sol perform well in the CMP polishing process. Specifically, silica sol polishing liquid can effectively reduce surface roughness and damage layer depth, improve polishing consistency and material removal rate, and at the same time has good fluidity, which is conducive to cleaning and chip removal after polishing.
[0004] However, despite the many advantages of silica sol in CMP polishing, it still faces some problems and defects in practical applications. First, due to the strong interaction between nano-SiO2 particles, existing silica sol is prone to agglomeration, resulting in uneven distribution of particles in the polishing liquid, affecting the polishing effect. Secondly, silica sol is prone to precipitation or stratification under conditions such as long-term storage, affecting the stability and service life of the polishing liquid.
[0005] Therefore, in view of the above problems, it is urgent to develop a high-purity silica sol for chemical mechanical polishing and a preparation method thereof, wherein the silica sol has the characteristics of being difficult to agglomerate and difficult to settle, and has the advantage of a good polishing effect. Summary of the invention
[0006] In view of the defects of the above-mentioned prior art, an object of the present invention is to provide a high-purity silica sol for chemical mechanical polishing and a preparation method thereof, aiming to solve the technical problems of the existing silica sol being easy to agglomerate, easy to settle and having poor polishing effect.
[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] A high-purity silica sol for chemical mechanical polishing is obtained by reacting the following components in parts by mass:
[0009] 100 parts of silicone monomer
[0010] Sodium polyacrylate 1-3 parts
[0011] 4-15 parts of tridecafluorooctyl triethoxysilane
[0012] Solvent 100-250 parts
[0013] Catalyst 0.1-5 parts by mass.
[0014] The organosilicon monomer is selected from at least one of ethyl orthosilicate, methyltriethoxysilane and dimethyldimethoxysilane;
[0015] Preferably, the mass ratio of the sodium polyacrylate to tridecafluorooctyltriethoxysilane is 1:(3-5);
[0016] More preferably, the mass ratio of the sodium polyacrylate to tridecafluorooctyltriethoxysilane is 1:4;
[0017] The solvent is a mixture of ethanol and deionized water, and the mass ratio of ethanol to deionized water is 1:(1.5-3);
[0018] Preferably, the mass ratio of the ethanol to deionized water is 1:2.
[0019] The catalyst is an aqueous ammonia solution.
[0020] The second object of the present invention is to provide a method for preparing the above-mentioned high-purity silica sol for chemical mechanical polishing, comprising the following preparation steps:
[0021] (1) According to the above formula, the organosilicon monomer, sodium polyacrylate, tridecafluorooctyl triethoxysilane, solvent and catalyst are weighed;
[0022] (2) Add solvent to the container, start stirring, add catalyst to adjust the pH of the system to 9-10, add organosilicon monomer dropwise while stirring, and stir under step temperature control to carry out hydrolysis and polycondensation reaction for 2-8 hours, then add sodium polyacrylate, stir and react at 95° C. for 2-3 hours, then add tridecafluorooctyl triethoxysilane and continue to stir and react at 95° C. for 2-3 hours to obtain high-purity silica sol for chemical mechanical polishing.
[0023] Preferably, the step temperature program is to react at 60-80°C for 2-3 hours, and then react at 85-90°C for 2-5 hours.
[0024] The third object of the present invention is to provide a chemical mechanical polishing solution, which comprises the above-mentioned high-purity silica sol for chemical mechanical polishing.
[0025] The fourth object of the present invention is to provide an application of high-purity silica sol for chemical mechanical polishing to improve the polishing effect of chemical mechanical polishing liquid.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] (1) The inventor creatively adds sodium polyacrylate and tridecafluorooctyl triethoxysilane to the system of high-purity silica sol for chemical mechanical polishing. On the one hand, the carboxyl groups on the sodium polyacrylate molecular chain form hydrogen bonds with water molecules, adsorb on the surface of particles, and prevent particle aggregation through electrostatic repulsion and steric hindrance, thereby maintaining the stable dispersion of silica particles in the solvent; on the other hand, tridecafluorooctyl triethoxysilane is used as a fluorine-containing silane with low surface energy, and the fluorine-containing end groups can repel each other after reaction on the surface of silica particles, so that the silica sol is stably dispersed. At the same time, the synergistic effect of sodium polyacrylate and tridecafluorooctyl triethoxysilane is used to jointly bring about a better average particle size (70nm-80nm) of the silica sol, a relatively narrow particle size distribution, i.e. a relatively small span (≤0.13), better sedimentation resistance (no precipitation occurs in a three-month storage stability test), and better polishing effect.
[0028] (2) The inventors creatively adopted a step-by-step temperature increase procedure in the process of preparing silica sol, first reacting at a low temperature for a certain period of time, and then heating to a high temperature for a certain period of time. The growth rates of the silicon dioxide microparticle nuclei at different temperatures are different, so that the final silica sol has a uniform particle size, a narrow particle size distribution, is not easy to agglomerate and settle, and has a good polishing effect. DETAILED DESCRIPTION
[0029] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0030] The raw materials are selected as follows:
[0031] The organosilicon monomer is tetraethyl orthosilicate (TEOS);
[0032] Sodium polyacrylate is Sokalan PA 25CL-FR from BASF;
[0033] Tridecafluorooctyltriethoxysilane is S00805 from Shanghai Shiyang Chemical Co., Ltd.;
[0034] The solvent was a mixture of ethanol and deionized water in a mass ratio of 1:2;
[0035] The catalyst is ammonia.
[0036] Example 1
[0037] A high-purity silica sol for chemical mechanical polishing is prepared by reacting the following components in parts by weight:
[0038] The first step is to weigh each raw material according to the following mass parts:
[0039] TEOS 100 copies
[0040] 2 parts of sodium polyacrylate
[0041] 6 parts of tridecafluorooctyl triethoxysilane
[0042] Solvent (a mixture of ethanol and deionized water in a mass ratio of 1:2) 150 parts
[0043] 1.5 parts ammonia
[0044] The second step is hydrolysis reaction:
[0045] Add solvent to the container, start stirring, add ammonia water to adjust the pH value to 9.5, add TEOS dropwise while stirring, keep the reaction at 60°C for 3 hours, then heat to 85°C for 3 hours, add sodium polyacrylate, stir and react at 95°C for 2 hours, then add tridecafluorooctyl triethoxysilane and continue to stir and react at 95°C for 3 hours to obtain high-purity silica sol for chemical mechanical polishing.
[0046] Example 2
[0047] A high-purity silica sol for chemical mechanical polishing is prepared by reacting the following components in parts by weight:
[0048] The first step is to weigh each raw material according to the following mass parts:
[0049] TEOS 100 copies
[0050] 2 parts of sodium polyacrylate
[0051] 8 parts of tridecafluorooctyl triethoxysilane
[0052] Solvent (a mixture of ethanol and deionized water in a mass ratio of 1:2) 150 parts
[0053] 1.5 parts ammonia
[0054] The second step is hydrolysis reaction:
[0055] Add solvent to the container, start stirring, add ammonia water to adjust the pH value to 9.5, add TEOS dropwise while stirring, keep the reaction at 60°C for 3 hours, then heat to 85°C for 3 hours, add sodium polyacrylate, stir and react at 95°C for 2 hours, then add tridecafluorooctyl triethoxysilane and continue to stir and react at 95°C for 3 hours to obtain high-purity silica sol for chemical mechanical polishing.
[0056] Example 3
[0057] A high-purity silica sol for chemical mechanical polishing is prepared by reacting the following components in parts by weight:
[0058] The first step is to weigh each raw material according to the following mass parts:
[0059] TEOS 100 copies
[0060] 2 parts of sodium polyacrylate
[0061] 10 parts of tridecafluorooctyl triethoxysilane
[0062] Solvent (a mixture of ethanol and deionized water in a mass ratio of 1:2) 150 parts
[0063] 1.5 parts ammonia
[0064] The second step is hydrolysis reaction:
[0065] Add solvent to the container, start stirring, add ammonia water to adjust the pH value to 9.5, add TEOS dropwise while stirring, keep the reaction at 60°C for 3 hours, then heat to 85°C for 3 hours, add sodium polyacrylate, stir and react at 95°C for 2 hours, then add tridecafluorooctyl triethoxysilane and continue to stir and react at 95°C for 3 hours to obtain high-purity silica sol for chemical mechanical polishing.
[0066] Example 4
[0067] A high-purity silica sol for chemical mechanical polishing is prepared by reacting the following components in parts by weight:
[0068] The first step is to weigh each raw material according to the following mass parts:
[0069] TEOS 100 copies
[0070] 1 part sodium polyacrylate
[0071] 4 parts of tridecafluorooctyl triethoxysilane
[0072] Solvent (a mixture of ethanol and deionized water in a mass ratio of 1:2) 150 parts
[0073] 1.5 parts ammonia
[0074] The second step is hydrolysis reaction:
[0075] Add solvent to the container, start stirring, add ammonia water to adjust the pH value to 9.5, add TEOS dropwise while stirring, keep the reaction at 60°C for 3 hours, then heat to 85°C for 3 hours, add sodium polyacrylate, stir and react at 95°C for 2 hours, then add tridecafluorooctyl triethoxysilane and continue to stir and react at 95°C for 3 hours to obtain high-purity silica sol for chemical mechanical polishing.
[0076] Example 5
[0077] A high-purity silica sol for chemical mechanical polishing is prepared by reacting the following components in parts by weight:
[0078] The first step is to weigh each raw material according to the following mass parts:
[0079] TEOS 100 copies
[0080] 3 parts of sodium polyacrylate
[0081] 12 parts of tridecafluorooctyl triethoxysilane
[0082] Solvent (a mixture of ethanol and deionized water in a mass ratio of 1:2) 150 parts
[0083] 1.5 parts ammonia
[0084] The second step is hydrolysis reaction:
[0085] Add solvent to the container, start stirring, add ammonia water to adjust the pH value to 9.5, add TEOS dropwise while stirring, keep the reaction at 60°C for 3 hours, then heat to 85°C for 3 hours, add sodium polyacrylate, stir and react at 95°C for 2 hours, then add tridecafluorooctyl triethoxysilane and continue to stir and react at 95°C for 3 hours to obtain high-purity silica sol for chemical mechanical polishing.
[0086] Comparative Example 1
[0087] A high-purity silica sol for chemical mechanical polishing is prepared by reacting the following components in parts by weight:
[0088] The first step is to weigh each raw material according to the following mass parts:
[0089] TEOS 100 copies
[0090] Solvent (a mixture of ethanol and deionized water in a mass ratio of 1:2) 150 parts
[0091] 1.5 parts ammonia
[0092] The second step is hydrolysis reaction:
[0093] Add solvent to the container, start stirring, add ammonia water to adjust the pH value to 9.5, add TEOS dropwise while stirring, keep the reaction at 60°C for 3 hours, then heat to 85°C for 3 hours to obtain high-purity silica sol for chemical mechanical polishing.
[0094] Comparative Example 2
[0095] A high-purity silica sol for chemical mechanical polishing is prepared by reacting the following components in parts by weight:
[0096] The first step is to weigh each raw material according to the following mass parts:
[0097] TEOS 100 copies
[0098] 10 parts of sodium polyacrylate
[0099] Solvent (a mixture of ethanol and deionized water in a mass ratio of 1:2) 150 parts
[0100] 1.5 parts ammonia
[0101] The second step is hydrolysis reaction:
[0102] Add solvent to the container, start stirring, add ammonia water to adjust the pH value to 9.5, add TEOS dropwise while stirring, keep the reaction at 60°C for 3 hours, then heat to 85°C for 3 hours, add sodium polyacrylate, and stir at 95°C for 2 hours to obtain high-purity silica sol for chemical mechanical polishing.
[0103] Comparative Example 3
[0104] A high-purity silica sol for chemical mechanical polishing is prepared by reacting the following components in parts by weight:
[0105] The first step is to weigh each raw material according to the following mass parts:
[0106] TEOS 100 copies
[0107] 10 parts of tridecafluorooctyl triethoxysilane
[0108] Solvent (a mixture of ethanol and deionized water in a mass ratio of 1:2) 150 parts
[0109] 1.5 parts ammonia
[0110] The second step is hydrolysis reaction:
[0111] Add solvent to the container, start stirring, add ammonia water to adjust the pH value to 9.5, add TEOS dropwise while stirring, keep the reaction at 60°C for 3 hours, then heat to 85°C for 3 hours, add tridecafluorooctyltriethoxysilane and stir at 95°C for 3 hours to obtain high-purity silica sol for chemical mechanical polishing.
[0112] Comparative Example 4
[0113] A high-purity silica sol for chemical mechanical polishing is prepared by reacting the following components in parts by weight:
[0114] The first step is to weigh each raw material according to the following mass parts:
[0115] TEOS 100 copies
[0116] 2 parts of sodium polyacrylate
[0117] 10 parts of tridecafluorooctyl triethoxysilane
[0118] Solvent (a mixture of ethanol and deionized water in a mass ratio of 1:2) 150 parts
[0119] 1.5 parts ammonia
[0120] The second step is hydrolysis reaction:
[0121] Add solvent to the container, start stirring, add ammonia water to adjust the pH value to 9.5, add TEOS dropwise while stirring, keep the reaction at 60°C for 6 hours, then add sodium polyacrylate, stir and react at 95°C for 2 hours, then add tridecafluorooctyl triethoxysilane and continue to stir and react at 95°C for 3 hours to obtain high-purity silica sol for chemical mechanical polishing.
[0122] Comparative Example 5
[0123] A high-purity silica sol for chemical mechanical polishing is prepared by reacting the following components in parts by weight:
[0124] The first step is to weigh each raw material according to the following mass parts:
[0125] TEOS 100 copies
[0126] 2 parts of sodium polyacrylate
[0127] 10 parts of tridecafluorooctyl triethoxysilane
[0128] Solvent (a mixture of ethanol and deionized water in a mass ratio of 1:2) 150 parts
[0129] 1.5 parts ammonia
[0130] The second step is hydrolysis reaction:
[0131] Add solvent to the container, start stirring, add ammonia water to adjust the pH value to 9.5, add TEOS dropwise while stirring, heat to 85°C to react for 6 hours, then add sodium polyacrylate, stir and react at 95°C for 2 hours, then add tridecafluorooctyl triethoxysilane and continue to stir and react at 95°C for 3 hours to obtain high-purity silica sol for chemical mechanical polishing.
[0132] Comparative Example 6
[0133] A high-purity silica sol for chemical mechanical polishing is prepared by reacting the following components in parts by weight:
[0134] The first step is to weigh each raw material according to the following mass parts:
[0135] TEOS 100 copies
[0136] 2 parts of sodium polyacrylate
[0137] 10 parts of tridecafluorooctyl triethoxysilane
[0138] Solvent (a mixture of ethanol and deionized water in a mass ratio of 1:2) 150 parts
[0139] 1.5 parts ammonia
[0140] The second step is hydrolysis reaction:
[0141] Add solvent to the container, start stirring, add ammonia water to adjust the pH value to 9.5, add TEOS dropwise while stirring, keep the reaction at 60°C for 3 hours, then heat to 85°C for 3 hours, add tridecafluorooctyl triethoxysilane, stir and react at 95°C for 2 hours, then add sodium polyacrylate and continue to stir and react at 95°C for 3 hours to obtain high-purity silica sol for chemical mechanical polishing.
[0142] Performance Testing:
[0143] Particle size determination: Laser nanoparticle size analyzer tests the average particle size and particle size distribution range. The particle size distribution range is characterized by span, span = (D 90 -D 10 ) / D 50 , a large span indicates a wide particle size distribution, and a small span indicates a narrow particle size distribution;
[0144] Anti-sedimentation performance: The silica sols of Examples 1-5 and Comparative Examples 1-6 were placed in a transparent container at room temperature for three months, and whether there was precipitation was observed regularly, and the time (days) when the silica sol precipitation occurred was recorded;
[0145] The silica sol of Examples 1-5 and Comparative Examples 1-6, polyvinyl pyrrolidone (PVP), tetramethylammonium hydroxide (TMAH), chelating agent (EDTA), and deionized water were mixed and stirred at a mass ratio of 30:0.5:0.5:0.3:68.7, and then the silicon wafer was subjected to chemical mechanical polishing using a UNIPOL-1203 chemical mechanical polishing machine and a synthetic leather polishing pad, and the polishing pressure was set to 200 kPa, the speed was 60 r / min, and the polishing time was 30 min. The surface roughness Ra of the sapphire substrate was then measured to characterize the polishing effect of the silica sol of the present invention.
[0146] The test results are shown in Table 1-2 below:
[0147] Table 1
[0148]
[0149] Table 2
[0150]
[0151] By comparing Examples 1-5 in Table 1 with Comparative Examples 1-6 in Table 2, it can be seen that the high-purity silica sol for chemical mechanical polishing of the present invention is added with sodium polyacrylate and tridecafluorooctyl triethoxysilane, and a step-by-step temperature increase program is adopted in the hydrolysis process of the silica sol, so that the high-purity silica sol for chemical mechanical polishing obtained in the end has a better average particle size (70nm-80nm), which is suitable for chemical polishing; the relatively narrow particle size distribution, that is, the relatively small span (≤0.13), indicates that the silica sol obtained by the present invention is not easy to agglomerate during the preparation process; better sedimentation resistance (can withstand three months of storage stability test without precipitation), indicating that the silica sol of the present invention has the characteristic of not being easy to settle; the silicon wafer has a lower surface roughness (Ra≤0.11) after polishing the silicon wafer, indicating that the silica sol of the present invention has a better polishing effect on the silicon wafer treatment.
[0152] By comparing Examples 1-5 in Table 1 with Comparative Examples 1-3 in Table 2, it can be seen that sodium polyacrylate and tridecafluorooctyl triethoxysilane play a synergistic role in the silica sol system, so that the high-purity silica sol for chemical mechanical polishing obtained has a better particle size range, is not easy to agglomerate, is not easy to settle, and has a better polishing effect. Among them, when the mass ratio of sodium polyacrylate to tridecafluorooctyl triethoxysilane is 1:4, all properties are optimal.
[0153] By comparing Examples 1-5 in Table 1 with Comparative Examples 4-5 in Table 2, it can be seen that when a step-by-step temperature increase program is not used in the preparation process of the silica sol, when only a reaction temperature of 60°C for 6 hours or a reaction temperature of 80°C for 6 hours is used, due to the different formation rates of silica particles at different temperatures and the different agglomeration tendencies between the particles, various performances are deteriorated compared to when a step-by-step temperature increase program is used.
[0154] By comparing Examples 1-5 in Table 1 with Comparative Example 6 in Table 2, it can be seen that when the order of adding sodium polyacrylate and tridecafluorooctyl triethoxysilane is changed during the preparation of the silica sol, when tridecafluorooctyl triethoxysilane is added first and then sodium polyacrylate, the various properties are relatively poor. This may be because the sequence of the two is related to the properties of the protective layer finally formed on the surface of silica due to the differences in chain length and steric hindrance.
[0155] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the embodiments of the present invention rather than to limit them. Although the embodiments of the present invention have been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the embodiments of the present invention can still be modified or replaced by equivalents, and these modifications or equivalent replacements cannot cause the modified technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-purity silica sol for chemical mechanical polishing, characterized in that: Obtained by reacting the following components in parts by mass: 100 parts of silicone monomer Sodium polyacrylate 1-3 parts 4-15 parts of tridecafluorooctyl triethoxysilane Solvent 100-250 parts Catalyst 0.1-5 parts by mass; The mass ratio of the sodium polyacrylate to tridecafluorooctyltriethoxysilane is 1:(3-5).
2. The high-purity silica sol for chemical mechanical polishing according to claim 1, characterized in that: The organosilicon monomer is selected from at least one of ethyl orthosilicate, methyltriethoxysilane and dimethyldimethoxysilane; The solvent is a mixture of ethanol and deionized water; The catalyst is an aqueous ammonia solution.
3. The high-purity silica sol for chemical mechanical polishing according to claim 2, characterized in that: The mass ratio of ethanol to deionized water is 1:(1.5-3).
4. The high-purity silica sol for chemical mechanical polishing according to claim 3, characterized in that: The mass ratio of the sodium polyacrylate to tridecafluorooctyl triethoxysilane is 1:4; The mass ratio of ethanol to deionized water is 1:
2.
5. A method for preparing a high-purity silica sol for chemical mechanical polishing according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following preparation steps: (1) Weighing the organosilicon monomer, sodium polyacrylate, tridecafluorooctyl triethoxysilane, solvent and catalyst according to the formula of claim 1; (2) Add solvent to the container, start stirring, add catalyst to adjust the pH of the system to 9-10, add organosilicon monomer dropwise while stirring, and stir under step temperature control to carry out hydrolysis and polycondensation reaction for 2-8 hours, then add sodium polyacrylate, stir and react at 95° C. for 2-3 hours, then add tridecafluorooctyl triethoxysilane and continue to stir and react at 95° C. for 2-3 hours to obtain high-purity silica sol for chemical mechanical polishing.
6. A method for preparing high-purity silica sol for chemical mechanical polishing according to claim 5, characterized in that: The step temperature program is to react at 60-80°C for 2-3 hours, and then react at 85-90°C for 2-5 hours.
7. A chemical mechanical polishing liquid, characterized in that: The chemical mechanical polishing liquid comprises the high-purity silica sol for chemical mechanical polishing as claimed in any one of claims 1 to 4 or the high-purity silica sol prepared by the preparation method of the high-purity silica sol for chemical mechanical polishing as claimed in any one of claims 5 to 6.
8. Use of the high-purity silica sol for chemical mechanical polishing according to any one of claims 1 to 4 or the high-purity silica sol for chemical mechanical polishing prepared by the preparation method according to any one of claims 5 to 6 to improve the polishing effect of chemical mechanical polishing liquid.
Citation Information
Patent Citations
Improved processing compositions and method of forming the same
CN101410461A
Silica sol for ceramic coating and preparation method thereof
CN117925102A
Super-hydrophobic anticorrosive material prepared based on silicon dioxide as well as preparation method and application of super-hydrophobic anticorrosive material
CN118460029A
Cited By
Silica sol with long-term stability and preparation method thereof
CN120841528A
Silica sol having long-term stability and method for preparing the same
CN120841528B